Towards Competency based Education - Gupta, M. Sen (JOURNAL OF INDIAN EDUCATION, 2020)
As per National Curriculum Framework (NCF) 2005, learners construct their own knowledge when they are active in the process of learning. This of course requires a participatory classroom ethos where the teacher stimulates the thinking and imagination of the learners and simultaneously challenges and motivates them for self directed learning. The National Education Policy 2020 repeatedly emphasises the need to nurture creativity, encourage innovativeness and develop entrepreneurship. According to the policy document, classroom transactions must shift towards competency based learning and education. This implies that the school curriculum has to emphasise experiential learning and develop in students the right kind of knowledge, skills, attitudes and values in order to enable them to face successfully the challenges posed by the rapid scientific advancement and technological development. It is in this perspective that the present article discusses the concept of competency, developing competency based curriculum and its distinctive features. It nicely illustrates how this curriculum helps the learner by giving remedial instruction, additional information and more time to practice.